A flexible model for efficient employee participation in UK companies. Issue 2 (2nd July 2020) - Kokkinis, Andreas; Sergakis, Konstantinos
ABSTRACT: Corporate contractarian literature dismisses employee participation as inefficient on the grounds that, if it were efficient, it would be voluntarily adopted widely. We argue that the scarcity of employee participation in the UK can be attributed to shareholder short-termism and behavioural biases and, therefore, that the question of its efficiency remains open for companies that want to explore this possibility. We thus propose a flexible approach that UK companies can follow to implement employee participation. Our approach takes into account the broader UK institutional framework by creating adaptable and long-term solutions for both listed and large private companies. We argue that the most pragmatic way to encourage efficient employee participation is through the introduction of formal employee advisory panels and, in the longer term, the proliferation of employee share ownership schemes coupled with special rights to appoint a number of directors in tandem with the size of employee share ownership.